4-degree-of-freedom voice-controlled robotic arm - Oyelami, Adekunle Taofeek; Elegbeji, Wahab Fisayo; Adeniyi, Oluwabukunmi (Institute of Advanced Engineering and Science, 2023)
People with impairments who utilize robotic arms have a great deal more independence in their daily lives. The robotic arm can help persons with specific needs by using voice control, which is practical. The working mechanism is fashioned to have four degrees of freedom (4-DOF) with the inclusion of a jaw or gripper. The Arduino microcontroller, the speech module, and the arm are the main components of the robotic arm, which is a lightweight model driven by four motors. The servo motor is used to supply the rotational motion in the arm’s three rotary joints and end effector. Rotation in two directions is made possible by the geared DC motors employed, which alter their direction of rotation if the polarity is flipped. The automatic voice recognition technology aids in comprehending spoken words picked up by a microphone. The HM2007 processor, the brains of the speech recognizer, is necessary for the speech recognizer to function. Digital commands are created from analog speech input. These commands are used as input to the Arduino thereby resulting in a system whereby the human voice gives a continuous control signal to operate a real and functional robotic arm.